1
$\begingroup$

We have $$\begin{cases} u_t + x^2 u_x = 0\\ u(x,0) = x \end{cases}$$ I found that the general solution is $$u(x,t) = f\left(-\frac{1}{x} - t\right)$$ Applying the initial condition $$u(x,0) = f\left(-\frac{1}{x}\right) = x$$ Then I thought we would have $$u(x,t) = -\frac{1}{x} - t$$ which checks out but it does not satisfy the initial condition. So I am wondering where I went wrong.

$\endgroup$
  • 2
    $\begingroup$ Well, if $f\left(-\frac{1}{y}\right) = y,$ as you have shown, then $f\left(-\left(\frac{1}{x} + t\right)\right) = f\left(-\frac{(1+tx)}{x}\right) = \frac{x}{1 + tx}$. Essentially, $f$ acts on the entirety of its input, it doesn't magically know that some part comes from $x$ and behave differently on just that part. $\endgroup$ – stochasticboy321 Jun 30 '17 at 17:25
  • $\begingroup$ @stochasticboy321 Can you explain this further I still do not understand $\endgroup$ – justanewb Jun 30 '17 at 19:47
  • $\begingroup$ $f$ is a function of a single variable. You want to determine $f(u),$ where $u = -(x^{-1} + t)$ is your canonical variable. You found that for any input, say $y$, $f(-1/y) = y$. Therefore, $f(u) = -1/u$. Now plug in the value of $u$ in terms of $x,t$. The idea is that $f$ is a map from $\mathbb{R}$ to $\mathbb{R}$. It cannot sniff out that the argument given to it is composed of two different variables. Analogously, suppose $g(x) = x^2.$ What is $g(2x)$? $g(xy)$? $\endgroup$ – stochasticboy321 Jul 1 '17 at 2:39
1
$\begingroup$

You correctly found that the general solution is $$u(x,t) = f\left(-\frac{1}{x} - t\right) \tag 1$$ Applying the initial condition $$u(x,0) = f\left(-\frac{1}{x}\right) = x$$ The goal is to determine the function $f$.

Let $\quad X=-\frac{1}{x}\quad\to\quad x=-\frac{1}{X}\quad$ , thus : $$f(X)=-\frac{1}{X}$$ Now the function $f$ is determined. We have to put it into equation (1) where the variable is $$\quad X=-\frac{1}{x} - t$$ This no longer $X=-\frac{1}{x}$ as above, since $t$ is no longer equal to $0$. $$f\left(-\frac{1}{x}-t\right)= -\frac{1}{-\frac{1}{x} - t}$$

$$u(x,t) = -\frac{1}{-\frac{1}{x} - t} = \frac{x}{1+xt}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.